Особливості формування нового світового порядку - Буць, Д. Є. (ХНУРЕ, 2022)
The article considers the problems of formation of the modern political world order. The world is entering a new era, the main features of which are the predominance of offensive nationalism, the rejection of formal and informal imperatives of sustainable behavior in the international arena, the destruction of deterrents, growing uncertainty and, as a result, increased risks and unpredictability in world politics. In the modern international system, some new parameters are being formed and it is important to assess their content component and their consequences for the development of the world community and the state of relations between the participants of international communication.
Keywords: світовий порядок